An Option-Based Approach to Measuring Disclosure Asymmetry - Smith, Kevin C. (The Accounting Review, 2023)
ABSTRACT In this paper, I develop a measure of the difference in the amount of information that investors expect a forthcoming disclosure to contain should it reveal good news versus bad news (the disclosure’s “asymmetry”). To do so, I first show that this asymmetry is linked to the skewness of returns that the disclosure creates. I then show that this skewness can be measured using a weighted change in option-implied return skewness leading up to the disclosure’s release. The measure’s ability to capture investors’ prior beliefs regarding asymmetry is advantageous when studying ex ante decisions including contracting and information acquisition choices. I implement it on a sample of large firms’ quarterly earnings announcements, finding evidence that investors anticipate cross-sectional but not time-series variation in earnings’ asymmetry.